2006
DOI: 10.1207/s15326942dn2901_8
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions in Becoming Writing Readers and Reading Writers: Note Taking and Report Writing in Third and Fifth Graders

Abstract: Results are reported for a study of 2 separate processes of report writing-taking notes while reading source material and composing a report from those notes-and related individual differences in executive functions involved in integrating reading and writing during these writing activities. Third graders (n = 122) and 5th graders (n = 106; overall, 127 girls and 114 boys) completed two reading-writing tasks-read paragraph (mock science text)-write notes and use notes to generate written report, a reading comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 18 publications
3
84
2
4
Order By: Relevance
“…Miyake and colleagues [32] established three core EF, inhibition, working memory (WM), and shifting, which provide a basis for the execution of more complex executive skills such as planning or problem-solving. EF have shown to be crucial for academic achievement such as reading and writing competence [1] and mathematics [9]. The emergence of EF has been linked to structural maturation of the frontal cortex [10].…”
Section: Introductionmentioning
confidence: 99%
“…Miyake and colleagues [32] established three core EF, inhibition, working memory (WM), and shifting, which provide a basis for the execution of more complex executive skills such as planning or problem-solving. EF have shown to be crucial for academic achievement such as reading and writing competence [1] and mathematics [9]. The emergence of EF has been linked to structural maturation of the frontal cortex [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, older children and adults were shown to access their analogue representation of numbers automatically (Girelli et al, 2000;Rubinsten et al, 2002). Moreover, several studies suggested that more automatic skills rely less on executive functioning (e.g., Altemeier, Jones, Abbott, & Berninger, 2006). Therefore, longitudinal studies would not only allow drawing stronger conclusions about the causal relations between executive functioning and the numerical magnitude skills, they would also help to clarify how these associations evolve along children's numerical development.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost is the link between executive function and math performance (Blair & Razza, 2007;Bull & Scerif, 2001;Butterworth, Varma & Laurillard, 2011;Cirino, 2010;Sabbagh, Xu, Carlson, Moses & Lee, 2006). Other research suggests a strong link between cognitive control and writing skills (Altemeier, Abbott & Berninger, 2008;Altemeier, Jones, Abbott & Berninger, 2006). Furthermore, pre-school children who are better able to exert effortful control to delay gratification score higher on cognitive achievement tests several years later in adolescence (Mischel et al, 1989).…”
Section: Classroom Engagementmentioning
confidence: 99%